(untitled) (Global Journal of Medical Research, 2014)
This case presentation describes a 19 years old female presenting with episodes of abnormal behavior in the form of singing and dancing. We assessed her mental and physical status as well as fully investigating her condition. She was diagnosed as Frontal lobe epilepsy and had shown good response to Lamotrigine.